Analisis Tingkat Religiusitas, Pendapatan & Kepercayaan Terhadap Kesadaran Membayar Zakat di Kota Tangerang - Anton Hindardjo; Abdul Wajid (STAI Asy-Syukriyyah, 2017)
The reliqiusity of analysis, earnings and awareness of pay zakat in Tangerang. The research aims to investigate the influence of awareness to pay zakat at Tangerang. Background of the study is there are lack of acceptance in zakat the data of central bureau of received at Baznas instutution at Tangerang, mean while Tangerang has statistic Tangerang has a good in come.The researcher used quantitative method by conducting questionnaire test to several government and others witch related questions about religiosity variable, income and trust increase awareness of paying zakat in Tangerang. In addition, the researcher do literature to support the theories will be discussed. The sample in this research is taken by using data collection method and purposive sampling. The number of samples were 77 respondents. The data obtained were analyzed by using PLS analysis technique through smart PLS software.The results of study, to investigate the relationship between religiosity and give positive afford of awareness of paying zakat were correlated, furthermore earning also have appositive effect on the increase of paying zakat. The results of this study give the less positive effect on conviction paying zakat.